Learning Cycle 9E Learning Model: How Does it Affect Students' Problem Solving Skills? - Anna Sintia; Nursilawati Nursilawati; Pina Rama Deani; Niken Diah Warastri; Desma Hemaliyah Apita; Nurul Azizah; Beti Susilawati (Action Research Journal Indonesia (ARJI), 2025)
Problem-solving skills are essential for achieving optimal learning outcomes. However, student participation in activities that develop these skills remains low, with only about 9% of students actively involved. This indicates a lack of self-confidence and a reluctance to express opinions or participate in discussions, which hinders the development of their problem-solving abilities. The Learning Cycle 9E instructional model is considered effective in enhancing these skills due to its clearly structured learning stages. This study aims to examine the effectiveness of the model in increasing student learning engagement at SMA Negeri 15 Bandar Lampung. The study employed a quantitative approach with a quasi-experimental design, involving class XII F1 as the experimental group and class XII F2 as the control group, both of which were randomly selected using the simple random sampling technique. The results of the normality test showed that the data in both groups were normally distributed (significance values of 0.077 for the experimental group and 0.647 for the control group). The t-test revealed a significance value of 0.590, indicating no significant difference between the two groups. However, students who were taught using the Learning Cycle model demonstrated better problem-solving abilities, were more engaged, and were more capable of applying their knowledge in real-life situations compared to those taught using direct instruction